The Effect of Leadership Style Strategy and Innovation Strategy on Competitive Advantages and Implementation of Industry 4.0 - Eko Wahyudi; Steph Subanidja (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2021)
The phenomenon of the Industrial Revolution 4.0 has become a global and national agenda in almost all countries of the world. The leadership style strategy and innovation strategy are expected to be able to create competitive advantage and Industry 4.0 implementation. This study aims to analyze the influence of variables to answer the question of how the leadership style strategy and innovation strategy can create competitive advantage and the implementation of Industry 4.0 in the manufacturing industry. This research provides theoretical implications as well as managerial implications regarding the strategic steps that Industry needs to take to implement Industry 4.0 through a leadership style strategy and an innovation strategy to create competitive advantage. The population in this study is the Medium and Large Industries engaged in the automotive, electronic and food and beverage industries which are spread in the districts of Bekasi, Karawang and Purwakarta, West Java Province of Indonesia.The result show there is a positive and significant influence between the leadership style strategy on innovation strategy, leadership style strategy on competitive advantage, innovation strategy on competitive advantage and leadership style strategy, innovation strategy as well as competitive advantage on Industry 4.0 implementation.